ДОСЛІДЖЕННЯ ІНДУКЦІЙНОГО НАГРІВАННЯ З’ЄДНАНИХ З НАТЯГОМ МЕТАЛЕВИХ ДЕТАЛЕЙ - Шидловський, А.К.; Жаркін, А.Ф.; Гориславець, Ю.М.; Новський, В.О.; Глухенький, О.І.; Бондар, О.І. (Інститут електродинаміки Національної академії наук України, 2018)
Mathematical model for numerical investigation of electromagnetic, heat and mechanical processes during induction heating of planted with tension metal details was proposed. Electromagnetic process in model is described by differential equations in terms of complex vector magnetic potential at applied voltage, that allow to coordinate directly induction system with power source. Heat problem is formulated as nonstationary equation of heat conductance with internal sources of heat from eddy currents, induced in material of details. Internally mechanical process presented by differential equation of mechanical equilibrium, solving of which allow determine thermomechanical tensions and deformations during heating. As an example the process of dismantling of aluminum disks from steel hub of the support roller of crawler vehicle have been investigated, namely the process of heating of details with the help of proposed electromagnetic system, that consist of two coils and common magnetic conductor. References 11, figure 4, table.